AFEX optimization of dacotah switchgrass and black locust. - Wong, Isaac Yi Siang. (2009)
Black Locust (Robinia pseudoacacia) is a pioneer plant, which has recently garnered attention for being a potential energy crop. Currently, there is very little information on the pretreatment and saccharification of Black Locust to produce fermentable sugars. This paper attempts to report the sugar yields from the enzymatic hydrolysis of Ammonia Fiber Expansion (AFEX) pretreated Black Locust, in comparison to AFEX pretreated Dacotah Switchgrass. Using a Box Behnken Surface Response Model, constrained optimal AFEX conditions of 1.5 NH3 loading (g NH3: g dry Biomass), 2.0 moisture content (g H20: g dry biomass), 150 °C and 30 min residence time have been selected as feasible pretreatment conditions, and have been predicted to achieve 60% glucose and 56% xylose yields for Dacotah Switchgrass. AFEX optimization for Black Locust using the same Box Behnken Surface Response Model approach is still underway.